LEGAL CERTAINTY OF THE DEED OF AGREEMENT MADE BY A NOTARY BASED ON THE POWER TO SELL (CASE STUDY CASE NUMBER: 41/PDT.G/2016/PN.PA) - Puspita Putri Ramadhani; Hasbir Paserangi; Wiwie Heryani (Indonesia Private Law Review, 2021)
Default is an omission or negligence, breaking a promise, or violating what has been agreed. One example of an engagement default is case number: 41/Pdt.G/2016/PN.PA. This case began with an agreement between Indoria Hi. The Mpasu brothers were represented by Alfian Chaniago as the authority holder with Lang Hartoyo and Rizal Tjahyadi through a letter of the agreement made by notary XX. Indoria Hi. The Mpasu brothers were unwilling to fulfill the agreement's contents and decided to cancel the agreement unilaterally because they felt they were never involved in the agreement. Based on the case above, a further question arises about how to guarantee legal certainty for authentic deeds and the consequences of the legal deed of agreement that does not follow the procedure. This study is normative legal research, which examines aspects of written law. The approach to the problem in this study is normative juridical, that is, it is based on applicable laws and regulations. In conclusion, the binding deed of the agreement made before a notary does not always go as expected. An authentic deed that does not meet formal requirements is considered imperfect, so it does not have an element of legal certainty. The legal consequence of the deed of the agreement under the power of attorney to sell that is not following the procedure is that the agreement will be null and void.